2010
DOI: 10.1186/1475-2867-10-36
|View full text |Cite|
|
Sign up to set email alerts
|

A cell-permeable dominant-negative survivin protein induces apoptosis and sensitizes prostate cancer cells to TNF-α therapy

Abstract: BackgroundSurvivin is a member of the inhibitor-of-apoptosis (IAP) family which is widely expressed by many different cancers. Overexpression of survivin is associated with drug resistance in cancer cells, and reduced patient survival after chemotherapy and radiotherapy. Agents that antagonize the function of survivin hold promise for treating many forms of cancer. The purpose of this study was to investigate whether a cell-permeable dominant-negative survivin protein would demonstrate bioactivity against pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…These results were consistent with our earlier results of the antitumor activities of SurR9-C84A. 12 Owing to the proliferative potential of SurR9-C84A in neurons with a low endogenous pool of survivin, differentiated SK-N-SH cells exhibited upregulation of cell-division markers. Endogenous survivin levels increased up to 46.3%, while PCNA and Ki67 showed a 5.1% and 24.9% increment, respectively.…”
Section: Protein Expressionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were consistent with our earlier results of the antitumor activities of SurR9-C84A. 12 Owing to the proliferative potential of SurR9-C84A in neurons with a low endogenous pool of survivin, differentiated SK-N-SH cells exhibited upregulation of cell-division markers. Endogenous survivin levels increased up to 46.3%, while PCNA and Ki67 showed a 5.1% and 24.9% increment, respectively.…”
Section: Protein Expressionsupporting
confidence: 93%
“…18,43 Several reports have confirmed that agents acting against survivin, such as small-molecule inhibitors, antagonists, and antisense agents, interfere with survivin expression or function and suppress tumor progression. 12,18,44,45 Studies have also reported that survivin overexpression is responsible for the resistance developed in advanced tumors. 5,46 Therefore, in a clinical setting, interfering with the functions of wild-type survivin results in strong antitumor activity, and for this purpose baculovirus inhibitory apoptotic protein repeat (BIR)-motif mutant SurR9-C84A-loaded NPs were employed against the neuroblastoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: sr9, cell-permeable dominant negative survivin surr9-c84a; chNP, chitosan nanoparticles; 3D, three-dimensional; smac, second mitochondria-derived activator of caspases; cIaP, cellular inhibitor of apoptosis. Although studies have been conducted with the C84A form of dominant negative survivin in both gene therapy 23 and protein therapy, 25 no interaction between the two forms of protein has been demonstrated. This is the first report that has showed interaction of dominant negative survivin protein SR9 with WT survivin in colon, liver, and breast cancer cells, and was further confirmed by Western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…24 The apoptotic effects of SR9 have been evaluated in prostate cancer cells where it sensitized the cells to tumor necrosis factor alpha (TNF-α) and induced apoptosis. 25 Recently, we have shown that SR9 displays dual actions: it is cytotoxic to cancerous cells and helps in proliferation of normal non-cancerous cells. This is because tumor cells have a high endogenous survivin pool, and treatment with SR9 leads to forceful survivin expression.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly the vaccine strategy proposed in 2013 (55) effectively suppresses MPM tumor growth in vivo without induction of autoimmune response and the cytotoxic activity induced by this vaccine proved to be specific for MPM cells (57). Furthermore survivin expression proved to be linked to resistance to chemotherapeutic agents, including vincristine, cisplatin, bortezomib, tamoxifen, paclitaxel, TNF-a and TRAIL in tumour cells (52,54) and it is also responsible of the suppression of radiation-induced apoptosis (50). Thus survivin-targeting in combination with anti-cancer drug could be useful to enhance the effect of chemotherapeutic agents and may be promising for mesothelioma treatment.…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%